FAKTOR HOST, KONSUMSI LEMAK, KONSUMSI KALSIUM DAN KEJADIAN HIPERTENSI PADA KEHAMILAN - Anindita Az Zahra Lutfiatunnisa; Anita Nugrahaeni; Sri Yuliawati; Dwi Sutiningsih (VISIKES: Jurnal Kesehatan Masyarakat, 2016)
Pregnancy induced hypertension is an increase of blood pressure until ≥140/90mmHg after 20 weeks of gestation among women who are previously normotensive. In the region of Gatak Community Health Center, in 2013 there were 47 cases of pregnancy induced hypertension which could lead to pre eclampsia and maternal and infant mortality. The objective of this study is to analyze the relationship between host factors, fat consumption and calcium consumption with pregnancy induced hypertension. This was an observational analytic with cross sectional study design. The subjects were 78 pregnant women in the region of Gatak Community Health Center using purposive sampling technique. Bivariate analysis performed using chi square. Bivariate analysis showed association between the level of knowledge (p=0.002; POR 4.91; 95%CI 1.69-14.27), history of hypertension (p=0.023; POR 3.75; 95%CI 2.58-5.46), nutritional status before pregnancy (p=0.004; POR 6.8; 95%CI 1.79-25.74), weight gainduring pregnancy (p=0.006; POR 7.58; 95%CI 1.75-32.78), consumption of fat (p=0.003; POR 6.43; 95%CI 1.71- 24.15), and calcium intake (p=0.014; POR 3.91; 95% CI 1.38-11.05) with pregnancy induced hypertension. A pregnant women should have normal nutritional status before pregnancy, normal weight gain during pregnancy, decrease consumption of fat and increase calsium intake to prevent pregnancy induced hypertension.Keywords: Hypertension, Pregnancy